Factors Affect Green Product Purchase Decisions: The Mediating Role of Green Brand Image (International Journal of Scientific Research and Management (IJSRM), 2024)
Research on environmentally conscious consumer behaviour requires particular attention to Asian markets. Although Vietnam is an Asian developing nation with a noted environmental conscience, little is known about their green product purchase habits and decisions. Thus, the goal of this study is to investigate the factors influencing Vietnamese consumers’ decisions regarding purchasing green products. The study evaluates a collection of theoretically proposed hypotheses using a convenience-based methodology. A 30-variable questionnaire was used to gather information from 347 residents. Exploratory and confirmatory factor analyses were used to analyse the data. The suggested theories were tested using structural equation modelling. The findings demonstrated that the customers were eager to support protecting the environment, aware of their environmental duties, and ready to look for information about sustainable goods. Supporting environmental protection, drive for environmental responsibility, green product experience, environmental friendliness of companies, social appeal, and green brand image are all recognised as significant variables that have a direct impact on consumers’ decisions to buy green products. Additionally, the study discovered that the association between these factors and decisions to purchase green products is mediated by the image of green brands. By investigating the variables influencing Vietnamese consumers’ preferences to buy environmentally friendly goods, this study offers insightful information on green purchasing habits in that country. The findings can help marketers create persuasive green marketing campaigns that highlight the environmental, social, and individual advantages aligned with the brand image linked to purchasing green products. These approaches will have positive impacts on their purchase decisions.